Relationship of Magic Mushroom Literation As A Drug With Abuse It's Use As A Hallucination - Yuri Rahayu; Andi Riyanto; Agung Wibowo (International Journal on Advanced Science, Education, and Religion, 2019)
Some cases consuming Magic mushroom resulting in death and behave strangelinto concerns. Literacy or knowledge of the dangers of this toxic fungus needs to be socialized so that communities especiallyteenagersdid not attempt to try to thrill to get satisfaction because of the nature of the hallucinations caused due by consuming Magic Mushroom. Magic mushroom contains the psilocin. This fungus is a narcotic class I inaccordance in enactment no. 35 year 2009. The purpose of this study is to know the correlation of literacy about magic mushrooms as a drug with the abuse behavior of teenagers as a Hallucinator in the area of Sukabumi City. The research method used is the quantitative research, with a formula of Association problems. The population of 19.284students with 392 number of sample, it's from high school and equivalent in Sukabumi region without differentiating classes and majors. Based on the results of the test indicate that there is a positive relationship between literacy of students about the magic mushroom with the behavior of misuse as Halusinasinator as evidenced by the value of 0.173> 005. The coefficient of this 0.173 describes a weak relationship.The results of the study provide guidance for the public, especially high school students that by having good knowledge of the dangers of the magic mushroom, students can avoid not consuming them and will maintain good behavior so as not to harm themselves and their environment.